Analyzing the intention of the households to drop off mobile phones to the collection boxes: empirical study in Malaysia - Rafia, Afroz; Muhibbullah, Muhammad; Fauzi, Puteri Farhana; Mohammad Niaz, Morshed (Emerald Group Publishing, 2020)
Purpose – To achieve proper waste management, the disposal of electronic waste (e-waste) is one suitable method. Most developing countries, including Malaysia, are facing lack of e-waste recycling facilities and low household participation. Using a survey method using a questionnaire, this study aims to examine the intention of Malaysian households to drop-off their mobile phones to the nearest collection boxes (n = 600). Design/methodology/approach – This study expanded the theory of planned behavior by adding environmental awareness and knowledge. In addition, the cost of disposal and the convenience of the available disposal infrastructure weremeasured as two parts of the perceived behavioral control. Findings – The results of this study show that environmental knowledge and awareness have a significant impact on attitudes toward recycling intention of the households. In addition, it was also found that the attitude and cost of disposal infrastructure is positively related to household intention. Originality/value – These results show that if e-waste collection boxes are provided to the nearest community and e-waste management information is distributed, this will increase household participation in e-waste management.